2015
DOI: 10.1210/en.2014-1797
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of an Ancestral Glycoprotein Hormone in the Pituitary of the Sea Lamprey, a Basal Vertebrate

Abstract: The gnathostome (jawed vertebrates) classical pituitary glycoprotein hormones, FSH, LH, and TSH, consist of a common α-subunit (GpA1) and unique β-subunits (Gpβ1, -2, and -3), whereas a recently identified pituitary glycoprotein hormone, thyrostimulin, consists of GpA2 and GpB5. This paper reports the identification, expression, and function of an ancestral, nonclassical, pituitary heterodimeric glycoprotein hormone (GpH) consisting of the thyrostimulin A2 subunit with the classical β-subunit in the sea lampre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The incorporation of a linker sequence between glycoprotein hormone subunits has been performed previously, and does not affect the assembly, secretion or bioactivity of human FSH (35), TSH (36) and CG (37). The conversion of two independent glycoprotein hormone subunits into a single polypeptide chain using a glycine-serine repeat linker sequence has also been performed recently with lamprey GPA2/GPB5 (38), which was shown to induce a cAMP response. Interestingly, similar proteins involving TSH alpha fused to TSH beta with carboxyl-terminal peptide (CTP) as a linker promoted a three-fold higher induction of cAMP compared to wild-type TSH, likely because the addition of a CTP linker increases protein stability and flexibility (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of a linker sequence between glycoprotein hormone subunits has been performed previously, and does not affect the assembly, secretion or bioactivity of human FSH (35), TSH (36) and CG (37). The conversion of two independent glycoprotein hormone subunits into a single polypeptide chain using a glycine-serine repeat linker sequence has also been performed recently with lamprey GPA2/GPB5 (38), which was shown to induce a cAMP response. Interestingly, similar proteins involving TSH alpha fused to TSH beta with carboxyl-terminal peptide (CTP) as a linker promoted a three-fold higher induction of cAMP compared to wild-type TSH, likely because the addition of a CTP linker increases protein stability and flexibility (39).…”
Section: Discussionmentioning
confidence: 99%
“…The ORFs of A. aegypti GPA2 and GPB5 sequences were tethered together in order to promote heterodimer interactions for testing in receptor activity assays with mammalian cell lines. A hexa-histidine tagged artificial linker sequence involving three glycine-serine repeats was used to fuse the amino-terminus of A. aegypti GPA2 propeptide sequence to the carboxyl-terminus of A. aegypti GPB5 prepropeptide sequence, using multiple PCR amplifications with several primer sets (Table S2) as performed previously using lamprey GPA2 and GPB5 sequences (38) (see SI Materials and Methods for details).…”
Section: Methodsmentioning
confidence: 99%
“…The only deiodinase characterized outside vertebrates has different chemical properties than the vertebrate ones in terms of specificity, as it acts on Triac rather than T3, the classical vertebrate TR ligand [56]. The hypothalamic-pituitary-thyroid endocrine axis was likely set-up at the basis of vertebrates [57,58]. All these innovations regarding the TH axis arise at the basis of vertebrates and may explain the acceleration of TR evolution in this group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must also be concluded that much structural information is still missing, such as from the TSHR-binding hormones [TSH, thyrostimulin (174176)], or TSHR structures themselves, or with bound allosteric ligands or intracellularly complexed partners. Moreover, combined with the missing information of the entire TSHR SD region or the full-length receptor with spatially adjusted domains, the molecular interpretation of functional data from mutagenesis studies or pathogenic findings is an approximation rather than a definitive answer so far.…”
Section: Available Structural Informationmentioning
confidence: 99%
“…Induction of the endogenous signal transduction by the TSHR is triggered extracellularly by TSH (191) or thyrostimulin binding (174176). The LRRD and the hinge region both harbor determinants for hormone binding [reviewed in Ref.…”
Section: Signal Transduction By Structural Reorganization: the Tshr Amentioning
confidence: 99%